Respuesta :

Transforming the function f(x) would change its formula to g(x)

The transformation of f(x) to g(x) are

  • Transform the function 2 units left
  • Transform the function 3 units up

How to determine the transformation?

The function is given as:

f(x) = e^x

Shift the function 2 units left

f'(x) = e^x + 2

Shift the function 3 units up

f''(x) = e^x + 2 + 3

Rewrite as:

g(x) = e^x + 2 + 3

Hence, the transformation of f(x) to g(x) are (b) and (c)

Read more about transformation at:

https://brainly.com/question/4057530

ACCESS MORE